PSYCHOLOGICAL AUTOPSY AS AN AUXILIARY TECHNOLOGY FOR BEHAVIOUR ANALYSIS AND POLICE INVESTIGATION - Pérez-Fernández, Francisco; Janosch-González, Heriberto; López-Muñoz, Francisco (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
After years of confusion and debate, the concept of ‘profiling’ has begun to fall into disuse and has been replaced by the more accurate term ‘behaviour analysis’. In reality, and in the face of decades of errors in the interpretation of his work, the behavioural analyst does not determine the ‘who’, but rather tries to unravel motivations in search of the ‘how’, the ‘why’ and the ‘what for’. From this technical-technological perspective, behaviour analysis procedures acquire an important criminalistic value as hypothesis-generating machinery to guide the work of field investigators, always fundamental and irreplaceable, in contexts of uncertainty. As the importance of understanding the role of the victim in criminal actions has become increasingly evident, the so-called psychological autopsy has re-emerged from among these analysis techniquestechnologies. This article attempts to show its importance and value of use, as well as to provide keys to help advance and consolidate it within the framework of behaviour analysis and criminal investigation techniques.